Entrepreneurial Leadership terhadap Innovative Work Behavior dengan Creative Self-Efficacy sebagai mediasi dan Proactive Personality sebagai moderasi - Maryati, Tri; Makarim, Habib Zhafran (Universitas Muhammadiyah Palembang, 2025)
This study aims to analyze, explain, and provide empirical evidence of the influence of entrepreneurial leadership on innovative work behavior with creative self-efficacy as a mediator and moderated by proactive personality in the food and beverage sector. This study was conducted on Warong Steak and Shake Yogyakarta, with a sample of 135 respondents, obtained through a questionnaire method selected with a non-probability sampling technique. The analysis method used is the Structural Equation Modeling (SEM) method using SmartPLS software version 4.0. The results of the study indicate that entrepreneurial leadership has a significant positive effect on innovative work behavior, entrepreneurial leadership has a significant positive effect on creative self-efficacy, creative self-efficacy has a significant positive effect on innovative work behavior, creative self-efficacy mediates entrepreneurial leadership on innovative work behavior, and proactive personality does not moderate entrepreneurial leadership on innovative work behavior